ANALYSIS ICON, INDEX AND SYMBOLS IN DAN BROWN'S THE DAVINCI CODE FILM AND NOVEL WITH CHARLES SANDERS PEIRCE THEORY - Ririn Kirana (IDEA : Jurnal Studi Jepang, 2023)
This research is entitled "Analysis Icon, Index and Symbols in Dan Brown's The DaVinci Code Film and Novel with Charles Sanders Peirce Theory". Semiotics is the study of signs. A sign is something that can be interpreted. All signs have various meanings in accordance with the existing conventions in society. This research is an attempt to identify and classify signs and then analyze the meaning of signs that appear in The DaVinci Code Films and Novels. There are several stages carried out in this study: preparation, data collection and data analysis. The data collected by the author is then explained about the type of sign as something that has meaning. The author uses Pierce's theory to identify, classify and analyze data. The results of this study indicate that there are three kinds of signs that appear in The DaVinci Code Film and Novel. That is the icon, index and symbol. The meaning of the signs varies with the context of each scene. The author hopes that this research will help readers to understand about semiotics, especially on the signs that are often found in our daily lives and how these signs can give meaning in communication.Keywords : Signs, Semiotic Analysis, Film, Novel